Examining the Development of Hadith Interpretation: Insights from Abu Rayyah, Juynboll, & Zakaria Ouzon - Zainuddin (UIN Sunan Kalijaga Yogyakarta, 2023)
This article aims to advance the field of hadith interpretation by examining the ideas of three influential figures: Abu Rayyah, Juynboll, and Zakaria Ouzon. Their distinctive approaches, characterized by both logic and critical analysis of traditional methods, resonate with contemporary trends in hadith hermeneutics studies. This makes them ideal subjects for exploring new avenues in hadith interpretation. By analyzing relevant literature, this research will explore the connections between these figures’ ideas and their impact on hadith scholarship. This analysis will then serve as the foundation for building a new framework for interpreting hadiths effectively. Their unique approach to evaluating both the chain of narrators (sanad) and the content of the hadith (matn) opens up fresh possibilities for a more dynamic and meaningful interpretation process (ijtihād). This means judging a hadith interpretation not only by who told it, but also by how well it aligns with the core values of the Qur’an and established scientific knowledge. Drawing inspiration from the work of Gadamer and Gracia, this research emphasizes the importance of skilled interpreters for understanding hadiths fully. By considering the broader context and implications of each hadith, this approach ensures interpretations remain relevant to the ever-changing world.